1992
DOI: 10.1063/1.106819
|View full text |Cite
|
Sign up to set email alerts
|

High-responsivity photoconductive ultraviolet sensors based on insulating single-crystal GaN epilayers

Abstract: We report on the fabrication and characterization of photoconductive ultraviolet detectors based on insulating single-crystal GaN. The active layer (GaN) was deposited over basal-plane sapphire substrates using a unique switched atomic-layer-epitaxy process. The sensors were measured to have a responsivity of 2000 A/W at a wavelength of 365 nm under a 5-V bias. The responsivity remained nearly constant for wavelengths from 200 to 365 nm and dropped by three orders of magnitude within 10 nm of the band edge (by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
156
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(161 citation statements)
references
References 7 publications
3
156
0
2
Order By: Relevance
“…A frequency dependence of the responsivity has also been detected [7] [11]. Reported data also indicate a very non-linear behavior, with a photoconductive gain decreasing with the optical power [5] [7]. In this work we present a study of the physical mechanism of photoconductive gain in GaN epitaxial layers, and the computer implementation of a novel model that matches our experimental results quite precisely.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…A frequency dependence of the responsivity has also been detected [7] [11]. Reported data also indicate a very non-linear behavior, with a photoconductive gain decreasing with the optical power [5] [7]. In this work we present a study of the physical mechanism of photoconductive gain in GaN epitaxial layers, and the computer implementation of a novel model that matches our experimental results quite precisely.…”
Section: Introductionmentioning
confidence: 52%
“…Some of the characteristics of GaN photoconductors have been reported. There is a general agreement on the presence of an abnormally high responsivity [5] [6] [9] and persistent photoconductivity [7] [10] [11], which have been tentatively attributed either to deep levels [9] or to Mg-doping related centers [8]. A frequency dependence of the responsivity has also been detected [7] [11].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A new market thus emerges in the field of telecommunications with High Electronic Mobility Transistors (HEMT's) which can support power densities 10 times higher than those accessible with the silicon and gallium arsenide technologies as reported by Dumka et al [6], as well as cut-off frequencies higher than 100 GHz were reported in a previous paper [7]. These HEMT's structures are essential to meet the increasing needs for the communication systems requiring high power and frequency applications [8][9][10] (radars, stations of bases, connection satellite). Due to their strong thermal conductivity and good performance stability in a hostile environment, GaN-based HEMT devices are excellent candidates especially in high power/frequencies domain.…”
Section: Introductionmentioning
confidence: 99%
“…These electronic and optoelectronic devices included visible light-emitting diodes (LED) [1], metal semiconductor field effects transistors (MESFET) [2], high electron mobility transistors (HEMT) [3], UV photoconductive detectors [4], and UV photovoltaic detectors [5]. The fabrication of the devices requires performing a controlled and reproducible n-and p-type doping.…”
Section: Introductionmentioning
confidence: 99%